Non-invasive assessment of gestational hemodynamics: benefits and limitations of impedance cardiography versus other techniques. (November 2013) - Staelens, Anneleen; Tomsin, Kathleen; Grieten, Lars; Oben, Jolien; Mesens, Tinne; Spaanderman, Marc; Jacquemyn, Yves; Gyselaers, Wilfried
To obtain data for maternal stroke volume and cardiac output during pregnancy, it is preferable to use a non-invasive, accurate and reproducible method. In this aspect, impedance cardiography is an excellent technique which is also highly accessible and easy to perform. This paper is a comprehensive review on the published literature about impedance cardiography and highlights the strengths and limitations of its applications in obstetrics.